ANALISIS PERLAKUAN AKUNTANSI BIAYA UNTUK JASA KONSULTANSI PENGAWASAN BERDASARKAN PSAK 34 TAHUN 2010 - Hayati, Sari; ., Lili (Buletin Studi Ekonomi, 2017)
This study aims to determine the cost of the recording system at PT Mandiri Aikon Survey to determine the accounting procedures used in the cost of financing the project. This research is a qualitative descriptive study, using primary data, secondary data, and data collection techniques by interview, observation and literature study, then analyzed using Statement of Financial Accounting Standards No. 34. The company is in calculating the cost of consultancy supervision use the completed contract method to recognize the cost. Completed contract method can be used to calculate revenue in the process of less than one accounting period, using the completed contract approach will provide a more reasonable so that the information presented is accurate. However, the calculations performed by the company not comply with the Statement of Financial Accounting Standards No. 34 in 2010, stated that the company should provide a more reasonable in recognizing the cost. All costs for the implementation of the bill work or progress is not recorded as revenue, but is accumulated in the account contract stating that the construction contract should be recognized respectively as income and expenses at the stage of completion of contract activity on neraca.Taksiran loss (expected loss) on the construction contract should be recognized as an expense